Magnetotactic bacteria in a droplet self-assemble into a rotary motor - Benoit Vincenti (Nature Portfolio, 2019)
It remains peculiar how to generate macroscopic work by harnessing the microscopic activity of living or synthetic agents like bacteria or micro-robots. Vincenti et al. show a biological rotary motor by self-assembling magnetotactic bacteria inside a droplet, producing a net torque on the droplet surface.